Istota strategii rozwojowych w praktyce polskich przedsiębiorstw - wyniki badań empirycznych - Zelek, Aneta (The Essence of Developing Strategies in Polish Enterprises' Practice - Empirical Results, 2008)
The paper presents some results of research project under the name of "The essence of strategic management in Polish enterprises' practices" that has been conducted on the sample of 250 companies in the West Pomeranian region, as the representative sample piloting the actual research in the scale of the whole Poland. The main goal of the project was verification of assumptions about certain practical dysfunctions and deformations in a strategic management process. The goal has determined the general consistency of the paper. Within the first part, the rationales of choosing the subject are presented. The part contains the review of professional literature on the strategic management defects as well. The second part of the paper includes the description of the purpose and the methodology of empirical research. The next parts are devoted to the presentation of the empirical results in four following threads: 1) survey of the strategy form (documentation, authors, event horizon, methods and periods of modification, forms of dissemination), 2) analysis and evaluation of strategic priorities and planning areas (mission/vision statements, strategic goals, planning areas), 3) types of used strategies examination (awareness of strategies classification), 4) strategy implementation problems and effects screening (analysis of attitudes towards strategy, strategic changes, achieved results). The paper finishes with an attempt to design the typical strategy profile and consequently with the catalogue of recommendations for Polish strategists.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 20, s. 465-489